Effects of Traditional Chinese Medicine acupuncture combined with rehabilitation nursing on improving recovery of limb motor function and self-care ability of stroke patients with hemiplegia (中医针灸及康复护理改善脑卒中偏瘫患者肢体功能和生活自理能力的效果观察) - HOU Xueru (侯雪茹); GENG Qingwen (耿庆文) (Journal of International Translational Medicine Limited, 2024)
Objective To investigate the effect of Traditional Chinese Medicine (TCM) acupuncture combined with rehabilitation nursing on improving recovery of limb motor function and self-care ability of stroke patients with hemiplegia. Methods Totally 70 stroke patients with hemiplegia were randomly divided into the study group and control group, with 35 cases in each group. All patients received routine rehabilitation treatment, including vital sign monitoring, prevention and treatment of complications, medication guidance and rehabilitation training. Patients in the study group were given TCM acupuncture combined with rehabilitation nursing. The Fugl-Meyer Assessment (FMA) scale was used to evaluate the limb motor function, and Barthel Index (BI) of Activity of Daily Living scale was used to evaluate patients' self-care ability. (P＜0. 05). Conclusion TCM acupuncture combined with rehabilitation nursing is effective to improve recovery of limb motor function, self-care ability and quality of life of stroke patients with hemiplegia. Results Scores of the FMA scale and BI were increased in both two groups after intervention, and scores of the FMA scale and BI in the study group were higher than those in the control group (目的 探讨运用中医针灸与康复护理干预改善脑卒中偏瘫患者肢体功能和生活自理能力的效果。方法 选取医院收治70例脑卒中偏瘫患者为研究对象, 随机分成研究组和对照组, 各35例。对照组患者接受常规康复理疗和护理, 包括生命体征监测、并发症防治、药物指导、康复训练等; 研究组在常规康复理疗和护理的基础上, 增加中医针灸和康复护理干预。采用Fugl-Meyer运动功能评分(FMA)评估患者躯体功能康复情况, 采用改良Barthel指数(BMI)评估患者日常生活活动能力。结果 干预后, 两组患者FMA和BMI评分均较干预前提高, 且研究组FMA和BMI评分高于对照组, 差异有统计学意义(P＜0. 05)。结论 中医针灸结合康复护理干预能有效改善脑卒中偏瘫患者临床症状, 促进其肢体功能康复, 提高日常自理能力, 从而改善患者生活质量。)